Feed intake, nutrients utilization and rumen metabolites concentration in sheep fed dry grass-Securinega virosa diet - SINGH, SULTAN; KARNAN, L K; KUNDU, S S (The Indian Journal of Animal Sciences, 2011)
Adult sheep (local x corridale~ 8) were offered dry mixed grass and Securinega virosa leaves in 50 : 50 proportion (% DM) in G1 vvhile sole S. virosa leaves were offered in G2â€¢ CP contents were 12.10 and 3.42% in S. virosa and grass respectively. Cell wall contents (NDF., ADF~ Cellulose and lignin) were higher in grass than S virosa leaves..Dry lnatter intake glkg wO.?5 was nonsignificantly higher in G1 than G2. DMD (%) was significantly high in G1 than 02. NDF and ADF digestibility (%) was comparable between the groups. However the CP digestibility (%) was nlore in 02 than Gt â€¢ TVFA concentration was similar between the groups. Total N concentration in G2 (100% S. virosa) was significantly higher than G1. Results revealed that sheep on grass-So virosa leaves in 50 : 50 ratio had higher intake, more nutrients digestibility and optinlum nitrogen metabolites concentration than sole feeding of S. virosa.Â